ESTUDO DA DEGRADAÇÃO DE CORANTE PRETO REATIVO 5 UTILIZANDO-SE FERRO DE VALÊNCIA ZERO - Lumbaque, Elisabeth Cuervo (2016)
In recent years have been generated innumerable cases of contamination in natural water bodies caused by different types of industry, highlighted water pollution from the textile effluents that are discharged directly into receiving bodies after inadequate treatment and or without treatment. In this context, there is a need to develop more efficient technologies and within of chemical processes applied to the treatment of textile effluents, oxidation and or reduction of pollutants present an attractive alternative for degradation efficiency compared to processes conventional. This way, the use of Fe0 as reducing agent of environmental pollutants has been studied and its main advantages are low toxicity, lower cost and high potential reductant (E0 Fe0/Fe2+ -0.440 V). This work studied the degradation of reactive black dye 5 using the Fe0 in three different matrices (powder, steel wool and nanoparticles immobilized in alginate) as a source for the occurrence of a reductive process and associating this process to Fenton and Fenton advanced system. The dye degradation studies using steel wool at pH 3.0 showed a high efficiency of the process 98 ±1.0 % of removal color in dye solution, when associated with Fenton process the degradation of aromatic intermediates formed was 93.55 ±1.0 % in 120 minutes of total reaction time. The removal of total organic carbon (TOC) was significant with 82.78% ± 1.0 furthermore ecotoxicity studies using biological indicators such as Lactuca sativa and Daphnia magna demonstrated that two processes combination do not present toxicity. The Fenton advanced system showed high degradation efficiency of the dye with 98% of discoloration at reaction times of 45 minutes.The synthesis and immobilization of the zero iron nanoparticles in alginate was efficient,metallic iron evenly distributed was within alginate beads and degradation studies with H2O2 at pH 5.0, obtain 70.3 ± 1.0 % of dye degradation and TOC reduction of 44.7 ± 1.0 % in 60 minutes. The Fenton advanced with steel wool was applied to the effluent from the textile industry obtaining 78.67% discoloration and a decrease of 69.57% in TOC. The results of this work are suitable for possible reuse of water in industry, besides reducing pollution and toxicity in the event of direct release into natural waters.